section "Roots of real quadratics"
theory Quadratic_Discriminant
imports Complex_Main
begin
definition discrim :: "[real,real,real] ⇒ real" where
"discrim a b c ≡ b⇧2 - 4 * a * c"
lemma complete_square:
fixes a b c x :: "real"
assumes "a ≠ 0"
shows "a * x⇧2 + b * x + c = 0 ⟷ (2 * a * x + b)⇧2 = discrim a b c"
proof -
have "4 * a⇧2 * x⇧2 + 4 * a * b * x + 4 * a * c = 4 * a * (a * x⇧2 + b * x + c)"
by (simp add: algebra_simps power2_eq_square)
with ‹a ≠ 0›
have "a * x⇧2 + b * x + c = 0 ⟷ 4 * a⇧2 * x⇧2 + 4 * a * b * x + 4 * a * c = 0"
by simp
thus "a * x⇧2 + b * x + c = 0 ⟷ (2 * a * x + b)⇧2 = discrim a b c"
unfolding discrim_def
by (simp add: power2_eq_square algebra_simps)
qed
lemma discriminant_negative:
fixes a b c x :: real
assumes "a ≠ 0"
and "discrim a b c < 0"
shows "a * x⇧2 + b * x + c ≠ 0"
proof -
have "(2 * a * x + b)⇧2 ≥ 0" by simp
with ‹discrim a b c < 0› have "(2 * a * x + b)⇧2 ≠ discrim a b c" by arith
with complete_square and ‹a ≠ 0› show "a * x⇧2 + b * x + c ≠ 0" by simp
qed
lemma plus_or_minus_sqrt:
fixes x y :: real
assumes "y ≥ 0"
shows "x⇧2 = y ⟷ x = sqrt y ∨ x = - sqrt y"
proof
assume "x⇧2 = y"
hence "sqrt (x⇧2) = sqrt y" by simp
hence "sqrt y = ¦x¦" by simp
thus "x = sqrt y ∨ x = - sqrt y" by auto
next
assume "x = sqrt y ∨ x = - sqrt y"
hence "x⇧2 = (sqrt y)⇧2 ∨ x⇧2 = (- sqrt y)⇧2" by auto
with ‹y ≥ 0› show "x⇧2 = y" by simp
qed
lemma divide_non_zero:
fixes x y z :: real
assumes "x ≠ 0"
shows "x * y = z ⟷ y = z / x"
proof
assume "x * y = z"
with ‹x ≠ 0› show "y = z / x" by (simp add: field_simps)
next
assume "y = z / x"
with ‹x ≠ 0› show "x * y = z" by simp
qed
lemma discriminant_nonneg:
fixes a b c x :: real
assumes "a ≠ 0"
and "discrim a b c ≥ 0"
shows "a * x⇧2 + b * x + c = 0 ⟷
x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a)"
proof -
from complete_square and plus_or_minus_sqrt and assms
have "a * x⇧2 + b * x + c = 0 ⟷
(2 * a) * x + b = sqrt (discrim a b c) ∨
(2 * a) * x + b = - sqrt (discrim a b c)"
by simp
also have "… ⟷ (2 * a) * x = (-b + sqrt (discrim a b c)) ∨
(2 * a) * x = (-b - sqrt (discrim a b c))"
by auto
also from ‹a ≠ 0› and divide_non_zero [of "2 * a" x]
have "… ⟷ x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a)"
by simp
finally show "a * x⇧2 + b * x + c = 0 ⟷
x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a)" .
qed
lemma discriminant_zero:
fixes a b c x :: real
assumes "a ≠ 0"
and "discrim a b c = 0"
shows "a * x⇧2 + b * x + c = 0 ⟷ x = -b / (2 * a)"
using discriminant_nonneg and assms
by simp
theorem discriminant_iff:
fixes a b c x :: real
assumes "a ≠ 0"
shows "a * x⇧2 + b * x + c = 0 ⟷
discrim a b c ≥ 0 ∧
(x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a))"
proof
assume "a * x⇧2 + b * x + c = 0"
with discriminant_negative and ‹a ≠ 0› have "¬(discrim a b c < 0)" by auto
hence "discrim a b c ≥ 0" by simp
with discriminant_nonneg and ‹a * x⇧2 + b * x + c = 0› and ‹a ≠ 0›
have "x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a)"
by simp
with ‹discrim a b c ≥ 0›
show "discrim a b c ≥ 0 ∧
(x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a))" ..
next
assume "discrim a b c ≥ 0 ∧
(x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a))"
hence "discrim a b c ≥ 0" and
"x = (-b + sqrt (discrim a b c)) / (2 * a) ∨
x = (-b - sqrt (discrim a b c)) / (2 * a)"
by simp_all
with discriminant_nonneg and ‹a ≠ 0› show "a * x⇧2 + b * x + c = 0" by simp
qed
lemma discriminant_nonneg_ex:
fixes a b c :: real
assumes "a ≠ 0"
and "discrim a b c ≥ 0"
shows "∃ x. a * x⇧2 + b * x + c = 0"
using discriminant_nonneg and assms
by auto
lemma discriminant_pos_ex:
fixes a b c :: real
assumes "a ≠ 0"
and "discrim a b c > 0"
shows "∃ x y. x ≠ y ∧ a * x⇧2 + b * x + c = 0 ∧ a * y⇧2 + b * y + c = 0"
proof -
let ?x = "(-b + sqrt (discrim a b c)) / (2 * a)"
let ?y = "(-b - sqrt (discrim a b c)) / (2 * a)"
from ‹discrim a b c > 0› have "sqrt (discrim a b c) ≠ 0" by simp
hence "sqrt (discrim a b c) ≠ - sqrt (discrim a b c)" by arith
with ‹a ≠ 0› have "?x ≠ ?y" by simp
moreover
from discriminant_nonneg [of a b c ?x]
and discriminant_nonneg [of a b c ?y]
and assms
have "a * ?x⇧2 + b * ?x + c = 0" and "a * ?y⇧2 + b * ?y + c = 0" by simp_all
ultimately
show "∃ x y. x ≠ y ∧ a * x⇧2 + b * x + c = 0 ∧ a * y⇧2 + b * y + c = 0" by blast
qed
lemma discriminant_pos_distinct:
fixes a b c x :: real
assumes "a ≠ 0" and "discrim a b c > 0"
shows "∃ y. x ≠ y ∧ a * y⇧2 + b * y + c = 0"
proof -
from discriminant_pos_ex and ‹a ≠ 0› and ‹discrim a b c > 0›
obtain w and z where "w ≠ z"
and "a * w⇧2 + b * w + c = 0" and "a * z⇧2 + b * z + c = 0"
by blast
show "∃ y. x ≠ y ∧ a * y⇧2 + b * y + c = 0"
proof cases
assume "x = w"
with ‹w ≠ z› have "x ≠ z" by simp
with ‹a * z⇧2 + b * z + c = 0›
show "∃ y. x ≠ y ∧ a * y⇧2 + b * y + c = 0" by auto
next
assume "x ≠ w"
with ‹a * w⇧2 + b * w + c = 0›
show "∃ y. x ≠ y ∧ a * y⇧2 + b * y + c = 0" by auto
qed
qed
end